The Processing Study Pora-Pora (Mystacoleuseus Padangesis) Liquid Smoke Smoke By Using Different Equipment Dryer Heat Source - Freddy Maruba; Syahrul '; Dahlia ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
This study was conducted in December 2013 in Technology Laboratory of Fishery, Fishery Products Chemistry Laboratory, Faculty of Integrated Laboratory of Fisheries and Marine Science, University of Riau, the purpose of research to evaluate the use of different heat sources on the quality of fish pora-pora (mystacoleuseus padangesis). Prepared in the manufacture of coconut shell liquid smoke, then smoke fish pora-pora dried with different heat sources (solar, electricity and gas) heat source is best analyzed for levels of protein, water, fat, peroxide and organoleptic value. The results showed that the use of the sun as a heat source in the fish processing pora-pora smoke is perlakuaan best with 9 hours of drying time, the protein content of 58.20%, water content of 10-15%, 23.58% fat content, peroxide number 1,90 meq/1000g sample and organoleptic value of 11.26%.Keywords: Tool dryer, heat in contrast, fish drying, fish pora-pora